Psychiatric Disorders in Children after Epilepsy Surgery: Acute, Subacute, and Chronic - Brooks, Garrett Andrew; Park, Jun Tae (Journal of Pediatric Epilepsy, 2018)
Psychiatric illness is highly prevalent among children with epilepsy and most commonly manifests as attentional deficits, mood dysregulation, and social isolation. While epilepsy surgery is increasingly utilized for seizure control in children with medically refractory epilepsy, its consequences with regard to psychiatric outcomes are still somewhat obscure. Epilepsy surgery may influence psychiatric outcomes in myriad ways, including through improved seizure control, decreased reliance on antiepileptic drugs, and by altering the course of a child's neurodevelopmental trajectory. This review surveys the current literature to elucidate the complex interactions between epilepsy surgery and psychiatric outcomes and attempts to delineate the progression of psychiatric manifestations in surgical patients over time. When compared with medical treatment, epilepsy surgery yields better social and behavioral outcomes in the early postoperative period; however, it is not clear that surgery is superior when assessing long-term social and behavioral metrics. Additionally, epilepsy surgery has shown promise in improving long-term cognitive outcomes, but these effects may not become apparent until several years after surgery. Moreover, longer preoperative seizure duration tends to be associated with worse psychiatric outcomes. Finally, surgical patients may be particularly vulnerable to the deleterious psychiatric effects of ongoing seizures.
Keywords: epilepsy surgery; behavior; cognition; psychiatric outcome; long term